Reproducibility and conflicts in immune epitope data. Issue 3 (5th February 2016) - Vita, Randi; Vasilevsky, Nicole; Bandrowski, Anita; Haendel, Melissa; Sette, Alessandro; Peters, Bjoern
Summary: The Immune Epitope Database is uniquely positioned to assess the body of research related to immune epitopes, we have manually curated all such published data. Thus, we are able to make observations on the state of these fields of research, as well as aggregate the individual data points to present a clearer picture of the immune response to specific antigens in all studied hosts. Additionally, we are able to identify where conflicts in the literature exist and where publications fall short in terms of identifiable methods and in reproducibility. Here we present guidelines to improve the quality of immune epitope data, which will benefit journals and researchers alike.